Pengaruh Model Pembelajaran terhadap Kemampuan Pemecahan Masalah - Seruni Seruni (Universitas Indraprasta PGRI, 2018)
The purpose of this research is to know the influence of model learning of mathematics problem-solving ability against learners Class VII in SMP Bogor Ibnu'Aqil. The methods used in this research was the quasi-experiment method. Whereas, his sample retrieval techniques is by random sampling technique with 60 students total sample taken from 2 classes, namely 30 students from the class of experiments are given treatment using cooperative learning model of type Two Stay Two Stray (TSTS) and 30 students from the class of the control that is named the treatment using a model of learning expository. Instrument in this study using reserved test essay totalling 7 problem after tested the validity of. Processing the data using SPSS 16.0 obtained test data requirements are normal and homogeny. The results of hypothesis testing come by sig 0.05, then < Ho is rejected, so it can be inferred that there was influence model of learning ability of mathematics problem solving towards learners in particular on the material covered.